PENGARUH PENERAPAN BAHAN AJAR BERMUATAN NILAI-NILAI KARAKTER DALAM MODEL PEMBELAJARAN SAVI TERHADAP KOMPETENSI FISIKA PESERTA DIDIK PADA MATERI MOMENTUM, IMPULS DAN GETARAN HARMONIS KELAS X MIPA SMAN 2 BUKITTINGGI - Rifka Oktaviani; Yulkifli Yulkifli; Murtiani Murtiani (PILLAR OF PHYSICS EDUCATION, 2017)
Achievement of the competence of learners on the subject of physics is not in accordance with the expected because of the mastery of physics students are still less and not actively involved in the learning process. In addition, the learning model used is still not diverse and teaching materials that have not been incorporated. Therefore, the researcher uses instructional materials values in SAVI learning model (Somatic, Audio, Visual, Intellectual). This study aims to apply the concept of teaching and learning in the learning model SAVI (Somatic, Audio, Visual, Intellectual) to the physics competence of students of class X MIPA SMAN 2 Bukittinggi.The type of research conducted is Quasi Experimental Research with Random Group Design Group design. The study population is the X class students from MIPA SMAN 2 Bukittinggi registered in the academic year 2016/2017, as many as 6 classes. Sampling was done by Purposive Sampling technique. The sample in this research is class X MIPA 4 as experiment class and class X MIPA 2 as control class. The data of this study include three properties, namely knowledge, attitude and skills. Assessment tools for learning, attitude observation sheets for attitudes, and performance appraisals for skills competencies. The data obtained were analyzed using two equity test equations for all competencies, a simple linear regression test and a real test level of 0.05 for knowledge competence and experimental class.The results show the average. Then the average is higher than the control class 78.3. The average level of learning skill classes is 85.64 higher than the control class. From the results of data analysis can be concluded that the application of teaching materials with character value gives a significant influence on the physics competence of students of class X SMAN 2 Bukittinggi to the competence of knowledge, attitude and achievement at the real level of 0.05